The Implementation of A Genre-Based Approach in Public Senior High Schools: A Study for Teacher Understanding - Bahri, Syamsul; Ariyani, Amra; Asma, Nurul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The research aims to know what the implementation of the genre-based approach in public senior high school 2 Gowa is. The focus of this research is on the teachers' comprehension of the Genre-Based Approach (GBA), their attitudes towards its implementation, and the creation of syllabi and lesson plans. The method used is qualitative research. We conducted the research at public senior high school 2 Gowa. The researcher collected the data through a combination of interviews, observations, and documentation. The researcher employs data analysis techniques that include data reduction, data presentation, and conclusion drawing. While teachers understand the application of the genre-based approach, they struggle to implement its steps. Teachers exhibit a positive attitude toward the implementation of GBA. The development of syllabi and lesson plans adheres to the planning and implementation steps, but it does not follow the evaluation and revision step. The teachers in this school encounter challenges stemming from the students' competence and motivation.